2011
DOI: 10.3892/ol.2011.417
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and mutagen sensitivity of epithelial cells and lymphocytes in oropharyngeal cancer

Abstract: Abstract. Tobacco-associated nitrosamines are known carcinogens causing DNA damage in epithelial cells of the head and neck. A matched case-control study was performed to evaluate the sensitivity of patients with squamous cell cancer (SCC) of the oropharynx, and controls to tobaccoassociated nitrosamines. Quantitative DNA repair was evaluated following a period of 15 and 30 min. Fresh biopsies from 100 male donors of macroscopically healthy oropharyngeal cells and lymphocytes (50 SCC patients and 50 controls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Moreover, 55% of the patients in our study who developed pneumonitis had a history of another malignancy. One may speculate that these patients had a reduced DNA repair capacity, which has been described for several tumor entities (21)(22)(23). In addition, a study from Italy that compared 43 breast cancer patients to 34 healthy controls has suggested that breast cancer was associated with an impairment of the DNA repair capacity resulting in an increased radio-sensitivity and radiation toxicity (24).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, 55% of the patients in our study who developed pneumonitis had a history of another malignancy. One may speculate that these patients had a reduced DNA repair capacity, which has been described for several tumor entities (21)(22)(23). In addition, a study from Italy that compared 43 breast cancer patients to 34 healthy controls has suggested that breast cancer was associated with an impairment of the DNA repair capacity resulting in an increased radio-sensitivity and radiation toxicity (24).…”
Section: Discussionmentioning
confidence: 92%
“…Bronchial asthma is a chronic inflammatory lung disease, and rheumatoid arthritis can also be associated with pulmonary involvement (25,26). The history of another tumor may be explained by a reduced DNA repair capacity, which has been described for several tumor types including lung cancer and can result in increased radio-sensitivity and radiation-related toxicity (27)(28)(29). The idea that patients developing radiation pneumonitis may have a reduced DNA repair capacity is further supported by the fact that the patients in our cohort had a poor prognosis in terms of progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of cellular integrity depends on the efficiency of multiple specific DNA repair pathways (reviewed in [ 47 ]) which are crucial in protecting against genomic instability, a characteristic of tumor development [ 48 ]. Genotoxic exposure to carcinogens such as tobacco often results in DNA damage that represents an important mechanism of OPSCC etiology [ 49 ]. Aberrant DNA methylation affecting the O6-methylguanine-DNA methyltransferases ( MGMT ) gene has been revealed in HPV-negative OPSCC [ 50 , 51 ], but also in lung cancer [ 52 ], suggesting the loss of the repair function of MGMT may reduce the ability of cells to repair DNA damage in smoking-induced tumors.…”
Section: Dna Methylationmentioning
confidence: 99%